A study on the capital accumulation system, distribution regulation mechanism and stakeholder relationships from the perspective of Marx's theory of ground rent - Di Xie; Ying Rong (China Political Economy (CPE), 2024)
Purpose - Ground rent has been playing a vital role in China's economic and social development, which has a clear practical logic. It is also necessary to present the historical inevitability and institutional mechanisms that realize this role of ground rent concerning its theoretical and historical logic. Design/methodology/approach - This paper draws on the theories of the French regulation school and the social structure of accumulation theory to establish a preliminary analytical framework. This paper explores the process of ground rent formation under certain land institutional arrangements, as well as the association between the capital accumulation system, the distribution regulation mechanism and relevant stakeholder relationships. From the perspective of historical materialism, the paper examines the functions of ground rent in feudal and capitalist societies and their mapping association between the capital accumulation system, distribution regulation mechanism and stakeholders. This paper further investigates the inevitable trends in the evolution of different social systems from the perspective of rent. Additionally, based on Marx's view on ground rent under socialism, the paper elucidates the formation, types of rent and its engagement in social production under the conditions of China's socialist market economy, identifying the inherent value orientation and distinct institutional advantages. Findings - Although considerable research has explored the reasons for the existence, categories and functions of rent in a socialist market economy, there is a relatively insufficient examination of its historical evolution and how it influences real-world economic dynamics. Existing studies have primarily focused on agricultural rent, lacking an in-depth analysis that puts the behaviors of landowners, land operators and laborers in fundamental contexts. Originality/value - As China enters a new stage of development, it is imperative to improve the public ownership of land from a new historical starting point, encourage the rational use of ground rent leverage, and establish and enhance the capital accumulation system, the distribution regulation mechanism and relevant stakeholder relationships, enabling their more harmonious alignment with the socialist market economy. The following effort should be made to ensure that such actions will be put into place.
Keywords: 330; Capital accumulation system; Ground rent; Regulation mechanism; Stakeholders